The Effects of Non-Genetic Factors on The Birth Weight, Litter Size and Pre-Weaning Survive Ability of Etawah Cross-Breed Goats in The Breeding Village Center in Ampelgading District - Tri Eko Susilorini; Kuswati Kuswati; Sucik Maylinda (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Universitas Brawijaya, 2017)
A total of 106 late gestation goats (age 4-5 months of pregnancy) records each of Etawah Crosbred goats kept on small farmer over a period of 10 years were assessed to determine the effects of environmental factors on them. Body Condition Score is non-genetic factor and in dairy goats to predicted milk production, fertility, and general health of the animal because BCS is visualisasi from feeding manajement. The objective of this study was to investigated the relationship between Body Condition Score (BCS) of late gestation with litter size and birth weight on etawah crossbred goats. The results showed that the average of litter size and birth weight (kg) were 1.89±0.66 and 3.84±0.73 respectively. The relationship between BCS with litter size were 0.13 (very low) and the relationship between BCS with birth weight were 0.11 (very low). The conclusion of this research is BCS of late gestation had positive correlation on litter size and birth weight, however this was low and birth weight as first indicator of future growth rate.